应用生物发光技术研究甲基硒酸对L9981-Luc肺癌细胞株移植瘤模型生长转移的影响 (Zhongguo Fei Ai Za Zhi, 2013)
BACKGROUND AND OBJECTIVE: Methylseleninic acid (MSA) is an artificially developed selenium compound. It has been proven that MSA could inhibit growth and metastasis on many tumor cells. This study investigated whether MSA has an impact on the growth and metastasis of L9981-Luc lung cancer transplanted model in nude mice or not. METHODS: A transplantated tumor model was established in nude mice. Fifteen nude mice were randomly divided into three groups: the control group treated with normal saline (0.2 mL/d), the MSA group treated with MSA solution (0.2 mL), and the cisplatin (DDP) group injected intraperitoneally with DDP (4 mg/kg/w). Inhibition of MSA on tumor growth and tumor metastasis was observed using the IVIS Imaging System 200 Series. RESULTS: A significant difference was obserced in the primary tumor bioluminescence among the three groups (P=0.002) on 21 days post-inoculation. Primary tumor bioluminescence in the DDP group (P=0.001) and in the MSA group (P=0.031) was significantly lower than that in the control group (P=0.001). No significant difference in the metastasis bioluminescence of the thoracic area was indicated among the three groups (P > 0.05). CONCLUSION: MSA can inhibit the growth of planted tumor of transgenic lung cancer cell lines L9981-Luc in nude mice. MSA may also suppress the distant metastasis of the transplanted tumor of transgenic lung cancer cell lines L9981-Luc in nude mice.